2004
DOI: 10.1537/ase.00067
|View full text |Cite
|
Sign up to set email alerts
|

Sexual determination of long bones in recent Japanese

Abstract: Sexual diagnosis of skeletons is of importance to physical and forensic anthropologists. The present study attempts to provide a basis from which one might choose a variable of a long bone that is most suitable in sexual assessments of skeletal material. A total of 47 variables of the humerus, radius, ulna, femur, and tibia of 64 recent-modern Japanese (32 male, 32 female) were investigated. The data were analyzed using the t-test and the stepwise discriminant analysis. The width of the articular surface of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 17 publications
4
55
1
8
Order By: Relevance
“…Thailand, China and Japan, Dittrick and Suchey studied the remains from Central California belonging to three cultural groups from 2500 BC, 1000-500 BC and after 500 AD. 10,[12][13][14][15][16] Finally, Kranioti investigated contemporary specimens from Crete and France European Americans, African Americans and Native Americans from the Tennessee data bank and found discriminant function analysis involving maximum length, head vertical diameter, minimum midshaft diameter and epicondylar breadth gave an accuracy of 91.1%. 17 Present study shows, the most discriminating variables included in the stepwise analysis are weight, total length, transverse diameter of head, circumference of midshaft, trochlear width and capitulum with 100% accuracy in males, 95% accuracy in females and 98.1% overall accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Thailand, China and Japan, Dittrick and Suchey studied the remains from Central California belonging to three cultural groups from 2500 BC, 1000-500 BC and after 500 AD. 10,[12][13][14][15][16] Finally, Kranioti investigated contemporary specimens from Crete and France European Americans, African Americans and Native Americans from the Tennessee data bank and found discriminant function analysis involving maximum length, head vertical diameter, minimum midshaft diameter and epicondylar breadth gave an accuracy of 91.1%. 17 Present study shows, the most discriminating variables included in the stepwise analysis are weight, total length, transverse diameter of head, circumference of midshaft, trochlear width and capitulum with 100% accuracy in males, 95% accuracy in females and 98.1% overall accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…1, 2 , Pablo Sebastián Giannotti 1, 2 , Horacio Chiavazza 3 y Gustavo Barrientos 1,4 Estimar el sexo a partir de huesos largos ha resultado de suma utilidad en muestras donde los indicadores clásicos, como la pelvis y el cráneo, se encuentran mal conservados, son fragmentarios o están ausentes (Black 1978;Mac Laughlin y Bruce 1985;Sakaue 2004;Šlaus 1997;Trancho et al 1997). Asimismo, en muestras procedentes de entierros secundarios u osarios, donde es necesario conocer el sexo de los huesos largos aislados para realizar reensamblajes de individuos (Byrd 2008), para hacer cálculos de número mínimo de individuos (Ubelaker 1974) y el número más probable de individuos (Adams y Konisberg 2004).…”
Section: Daniela Alit Mansegosaunclassified
“…De esta manera, surge la necesidad de elaborar modelos regionales específicos en un intento de mejorar la exactitud en la determinación del sexo. Además, la mayoría de las muestras óseas empleadas para desarrollar criterios de estimación sexual a partir de huesos largos han sido obtenidas de poblaciones asignadas cronológicamente entre los siglos XV y XX y son principalmente de ancestría europea, africana o asiática (Asala 2001; Di Bennardo y Taylor 1982; King et al 1998;Mall et al 2000;Purkait y Chandra 2004;Sakaue 2004;Šlaus y Tomičić 2005). Si bien estos criterios podrían llegar a ser útiles en muestras de poblaciones históricas, en muchos casos tenemos el problema de no conocer la ancestría de los individuos analizados.…”
Section: Daniela Alit Mansegosaunclassified
“…Dimensions from the upper long bones (humerus, radius, ulna, and clavicle) have been used to successfully distinguish between the sexes in several European (Cowal and Pastor 2008;Bašić et al 2013;Kranioti and Tzanakis 2015), Asian (Sakaue 2004;Lee et al 2014) and African populations (Steyn and Işcan 1999;Barrier and Abbé 2008). In mentioned studies, different measurements have been shown to be good indicators of sex dimorphism.…”
Section: Introductionmentioning
confidence: 99%